Sexual dimorphism, gonad structure and genetic differences of pink skunk clownfish (Amphiprion perideraion) - Sarmiza Saperi (Terengganu: Universiti Malaysia Terengganu, 2017)
Pink Skunk Clownfish, Amphiprion perideraion, is known as protandric hermaphrodite where it can change its sex from male to female. In order to breed clownfishes in captivity, they need to be paired which means the ability to identify the fish sex is crucial.